2023
DOI: 10.17219/acem/159089
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir-induced inflammatory and hydropic degenerative liver injury in rats

Abstract: Background. Favipiravir is very effective in the treatment of many viral infections, especially at high doses.It was used at such doses to treat coronavirus disease 2019 (COVID-19) during the pandemic. However, liver damage was reported in patients undergoing such treatment.Objectives. This study aimed to investigate the effects of low and high doses of favipiravir on the liver of rats, using biochemical and histopathological methods. Materials and methods.Wistar albino rats were allocated to one of 3 groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Additionally, the drug decreased endogenous antioxidant levels 15 . Similarly, Bilici et al reported that rats treated with a high dose of favipiravir exhibited increased oxidant and decreased antioxidant levels 26 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, the drug decreased endogenous antioxidant levels 15 . Similarly, Bilici et al reported that rats treated with a high dose of favipiravir exhibited increased oxidant and decreased antioxidant levels 26 .…”
Section: Discussionmentioning
confidence: 93%
“…Following the 1-h interval following the administration of drugs and distilled water, favipiravir was orally administered at a dosage of 800 mg/kg twice daily for seven days to all the animal groups except the HG group. Favipiravir is known to cause oxidative and inflammatory damage at high doses 26 . Lacidipine, TPP, and ATP were administered once daily for seven days.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5] Favipiravir has many toxic effects including diarrhea, hepatotoxicity, nephrotoxicity, decreased white blood cell count and neutrophil level, and nausea. [6] Lung tissue is an organ rich in blood supply, and cases of pulmonary intoxication due to drugs have been reported in the literature. [7,8] Not all therapeutic agents could directly cause cell toxicity.…”
mentioning
confidence: 99%